In vitro responses of two barley varieties to Moringa extract and growth regulators under drought stress - SAJA JAWAD SHNAISHEL BADAY; MAYADA TTARIQ AL-JUBORI Al-Jubori; MAHA IBRAHIM SALIH (Asian Journal of Agriculture, 2025)
Abstract. Baday SJS, Al-Jubori MT, Salih MI. 2025. In vitro responses of two barley varieties to Moringa extract and growth regulators under drought stress. Asian J Agric 9: 358-367. The world has recently turned to find alternatives to plant growth regulators, especially materials used in plant tissue culture, as they are the main pillar in establishing tissue cultures and participate in all stages of agriculture. Plant extracts from (seeds or leaves) are most important that can encourage growth, as they contain many active compounds that may compensate for hormones and increase the plant's resistance to drought. Moringa extract contains phenols, ascorbic acid, in addition to growth-promoting hormones (auxins, gibberellins and cytokinins), and abscisic acid, and the activities of the antioxidant enzymes (catalase, peroxidase, and superoxide dismutase). In the research, barley embryos were grown in the Murashige and Skoog (MS) culture media containing of Moringa leaf extract with (0, 1.5, 3 and 4.5 mL L-1), versus kinetin (Kin) treatments at 0, 1, 2 and 3 mg L-1 and indole acetic acid (IAA) at 0.5 mg L-1 then, plantlets that achieved highest average number of shoots, total chlorophyll and dry weight were transferred to the culture media containing Poly Ethelene Glycol (PEG) at 0, 2, 4 and 6 g L-1 and the work was performed from a fully Complete Randomized Design (CRD), the sample size on which the analysis was conducted was 160 samples resulting from the use of two varieties of barley, 4 concentrations of Moringa extract, 4 concentrations of Kin, and 5 replications. The results estimated that the highest average number of the vegetative shoots formed was 16.8 shoots plant-1, the total amount of chlorophyll was 323.4 mg g-1, and the dry weight of vegetative shoots was 88.9 mg in concentration 3 of Moringa and Kin extract in the Buhuth244 variety. The average plant relative growth rate was 49.2 mg day-1, and the average plant growth rate was 56.1 mg day-1 in Buhuth244, and 3 mL L-1 of Moringa extract and 4 of PEG. The examination, diagnosis, and estimation of the active compounds in the Moringa leaf methanolic extract was identified by Gas Chromatography with Mass Spectrometer unit (GC-MS). These extracts can serve as useful antioxidant materials. This study has concluded that Moringa extract can be used as an alternative to synthetic plant hormones due to its effect on improving vegetative growth characteristics.